TRANSMISSION ACCURACY OF SYNCHRONOUS BELT BASED ON RECURDYN - GUO JianHua; MENG QingXin; YU Xin; HU QingMing (Jixie qiangdu)
Using the mechanism of the tooth climbing of the belt,the mathematical model of the transmission error is established,reveals the transmission error of the synchronous belt is a function of the pulley pitch angle.Establish the virtual prototype dynamic transmission simulation model of synchronous belt based on Recur Dyn,through collect data and numerical analysis that mesh point with climbing tooth trace-Archimedes spiral,simulation results are consistent with the experimental results,to verify the accuracy of the simulation analysis.And compare the transmission accuracy of the new profile and L type trapezoidal tooth synchronous belt.The results showed that the transmission error of the new profile synchronous belt（Δθ =0.932mrad） less than L type trapezoidal toothed（Δθ = 1.615mrad）,shows that the capacity anti climbing tooth of the new profile synchronous belt is stronger than L type trapezoidal tooth,the tooth design of new profile synchronous belt is more reasonable.